Brain versus Reality: How Should Law Students Think? - Widyawati, Anis; Arifin, Ridwan; Rasdi, Rasdi (Indonesian Journal of Advocacy and Legal Services, 2021)
Law students are expected to have special abilities in the field of legal science, either in oral or oral. But in fact, the analytical skills of law students are not comparable to other abilities. Based on preliminary research conducted by the Proposer Team, it shows that out of 200 law students surveyed (Students of the Faculty of Law, Semarang State University), only 10 have written and conducted scientific publications in both national and international journals. Meanwhile, of the 200 people stated that students' critical abilities and analytical thinking are important, 184 people said that discussion forums are mandatory for law students, but in fact, of these 184 people, only 2 people followed up on the results of the discussion. . In other words, discussions conducted by students were not followed up in various forms of scientific studies and publications that could be read by many people. This program provides facilities for law students in in-depth critical analysis studies and criminal case studies related to human rights. In this program, students are expected to be able to have good analytical skills both in oral and verbal forms. Partners in this program are the law student community at Semarang State University. This program is expected to be able to solve partners' problems in the lack of critical analytical skills and case studies of criminal law as well as scientific publication of legal research results. The output of this program is expected to create a sustainable and sustainable activity related to critical analysis and legal case studies.